Rapid detailed spatial soil erosion mapping and risk assessment in Shivalik Hills, Punjab - GAHLOD, N.S.; MEENA, R.L.; BINJOLA, SONAM; DHARGAWE, S. D.; ., RAVI; KUMAR, DEVINDER; GAUTAM, RAVI; KULKARNI, RAVINDRA; TANEJA, RAJNI (Journal of Soil and Water Conservation, 2020)
Assessment of soil erosion risk is important for evaluating the soil loss dynamics in area. The present study was conducted in Geographic Information System (GIS) environment by using a framework of Erosion Risk Weightage Index (ERWI) model developed by Soil and Land Use Survey of India, Ministry of Agriculture and Farmers Welfare, Government of India. This model uses the soil and land attributes acquired through rapid detailed soils mapping as input and provide a rapid scientific, landscape-based framework for assessment of erosion risks in the face of growing challenges related to changing desertification status. The process involves development of image analysis map using IKONOS data with Cartosat- Digital Elevation Map (DEM) downloaded from BHUVAN. The mapping for soil and land parameters governing soil susceptibility to erosion were derived using High Resolution Satellite data at 1:5 K scale. The physically based model principally uses Runoff Potential Weightage values assigned on the basis of relative assessed runoff generated from the area covered by landscape based unit. The Runoff Potential Weightage is combined and reciprocal effect of set of soil, land and climate attributes used to spatially prioritize the entire study area into five soil erosion risk categories. The particle inertia factor K is taken as 0.50. This study confirms that out of total 225506 ha area, the area under very high erosion risk and high erosion risk is about 43322 ha and 37440 ha, respectively. Detailed spatial mapping aids in planning appropriate field level conservation measures to prevent the soil erosion and further degradation of land.